FAKTOR-FAKTOR YANG MEMPENGARUHI REMAJA USIA PRODUKTIF MELAKUKAN JUDI SABUNG AYAM - Feri Aprian; Berchah Pitoewas; M. Mona Adha (Jurnal Kultur Demokrasi, 2014)
The purpose of this research is to explain the factors that affect the productive age teenagers do the gamble cockfight, this research uses descriptive method quantitative sample with 65 people respondents, used is the percentage. Based on the analysis of the data revealed that family factor which belongs to the category high is 84,61%, belongs to the medium is 12,30%, and relatively low is 3.07%. The education factor which belongs to the category high is 33,84%, belongs to medium category is 53,84%, and classified as low is 12,30%.  While the social environmental factors caused by the relatively high 26,15%, classified as medium, as well as 58,46% belong to the category of low-15.38%.  So from the results of analysis it can be concluded that the influence factors of families occupying the highest positions followed, the education factor and social factors on the adolescent age of productive conducting cockfight gambling.Tujuan penelitian ini untuk menjelaskan faktor-faktor yang mempengaruhi remaja usia produktif melakukan judi sabung ayam, penelitian ini menggunakan metode deskriptif kuantitatif dengan sampel 65 orang responden, analisis data menggunakan teknik persentase. Berdasarkan analisis data diketahui faktor keluarga yang tergolong kategori tinggi 84,61%, tergolong sedang 12,30%, dan tergolong rendah 3,07%. serta faktor pendidikan yang tergolong kategori tinggi 33,84%, tergolong sedang 53,84%, dan tergolong rendah 12,30%. Sedangkan yang disebabkan oleh faktor lingkungan sosial yang tergolong tinggi 26,15%, tergolong sedang sebanyak 58,46%, serta yang tergolong kategori rendah sebesar 15,38%. Sehingga dari hasil analisis dapat disimpulkan bahwa pengaruh faktor keluarga menempati posisi tertinggi disusul, faktor pendidikan dan lingkungan sosial pada remaja usia produktif melakukan judi sabung ayam.Kata kunci : judi, remaja usia produktif, sabung ayam.